5^11 -(6x5^10-2x5^10)
^=puterea
Răspunsuri la întrebare
Răspuns de
4
Răspuns:
Explicație pas cu pas:
5¹¹ - ( 6 x 5¹⁰ - 2 x 5¹⁰ ) = 5¹⁰
= 5¹¹ - 5¹⁰ x ( 6 - 2 ) =
= 5¹¹ - 5¹⁰ x 4 =
= 5¹⁰ x ( 5 - 4 ) =
= 5¹⁰ x 1 =
= 5¹⁰
Răspuns de
1
5 ^ 11 - ( 6 × 5 ^ 10 - 2 × 5 ^ 10 ) =
5 ^ 11 - 5 ^ 10 × ( 6 - 2 ) =
5 ^ 11 - 5 ^ 10 × 4 =
5 ^ 10 × ( 5 - 4 ) =
5 ^ 10 × 1 = 5 ^ 10
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă